El picudo del algodonero - Ríos Medal, Ariel (Estelí (Nicaragua), 1978)
Sumario (Es)
6 ref.
Tesis (Tec Agr)
Keywords: GOáYPIUM HIRSUTUM; PLAGAS DE PLANTAS; CONTROL DE PLAGAS; CULTIVO; ANTHONOMUS GRANDIS; CONTROL CULTURAL; CULTIVOS TRAMPA; NICARAGUA